Algebraische Zahlentheorie: 7.8. bis 13.8.1988 - Jehne, Wolfram; Leopoldt, Heinrich-Wolfgang; Roquette, Peter (Tagungsbericht, 1988)
|Prof. Dr. J. A. Antoniadis, Iraklion; Dr. G.-M. Cram; W. Bosma, Amsterdam; Dr. C. Deninger, Regensburg; Dr. J. Brinkhuis, Rotterdam; Ur. G. R. Everest, Norwich; D. J. Burns, Cambridge UK; Prof. Dr. G. Frei-Imfeld, Quebec; Dr. C. J. Bushnell, London; Prof. Dr. G. Frey, Saarbrücken; Prof. Dr. A. Fröhlich, London; Prof. Dr. F. Halter-Koch, Graz; Prof. Dr. W.-D. Geyer, Erlangen; Dr. D. Haran, Tel Aviv; Prof. Dr. B. W. Green, Stellenbosch; Dr. Li. Jannsen, Regensburg; Prof. Dr. R. Greenberg, Seattle; Prof. Dr. M. Jarden, Tel Aviv; Prof. Dr. W. Jehne, Köln; Prof, Dr. H. Koch, Berlin; Prof. Dr. C. U. Jensen, Kobenhavn; Dr. W. Kohnen, Münster; Dr. E. Kani, Kingston; Dr. K. Komatsu, Regensburg; Dr. E. Kleinert, Köln; Prof. Dr. S. V. Kotov, Minsk; Prof. Dr. N. Klingen, Köln; F. -V. Kuhlmann, Heidelberg; Prof. Dr. E. Lamorecht, Saarbrücken; Prof. Dr. F. Lorenz, Münster; Prof. Dr. J.B. Leicht, Heidelberg; Prof. Dr. M. L. Madan, Columbus; Prof. Dr. H. W. Lenstra Jr., Berkeley; Dr. G. M. Malle, Berlin; Prof. Dr. H.-W. Leopoldt, Karlsruhe; Prof. Dr. M. Matignon, Talence; Prof. Dr. A. Leutbecher, München; Prof. Dr. B.H. Matzat; Berlin; Prof. Dr. W. Narkjewicz, Wroclaw; Dr. F. Pop, Heidelberg; E. Nart, Bellaterra; Dr. H.P. Rehm, Karlsruhe; Prof. Dr. J. Neukirch, Regensburg; Prof. Dr. J. Ritter, Augsburg; Prof. Dr. R. W. K. Odoni, Exeter; Prof. Dr. P. Roquette, Heidelberg; Prof. Dr. H. Opolka, Göttingen; Prof. Dr. K. Rubin, Columbus; Prof. Dr. R. Schertz, Augsburg; Prof. Dr. M. J. Taylor, Manchester; Dr. C.-G- Schmidt, Groningen; Prof. Dr. K. Wingberg, Erlangen; Prof. Dr. P. Schneider, Köln; Prof. Dr. H. G. Zimmer, Saarbrücken; P. Stevenhagen, Amsterdam
Keywords: Konferenzschrift